Launch of Food Security Simulator - Kenya: 6th KIPPRA Annual Regional Conference 2023 - Ecker, Olivier; Comstock, Andrew R.; Breisinger, Clemens; Ngugi, Rose; Simiyu, Fred (Kenya Institute for Public Policy Research and Analysis, 2023)
Launch of Food Security Micro-Simulation Tool KiPPRA and IFPRI